Unlocking Customer Loyalty in Indonesian Local Coffee Shops: An In-depth Analysis of The Influential Factors - Silalahi, Rudy Vernando; Novenson, Novenson (Jurnal Manajemen Bisnis, 2024)
Research aims: The purpose of this study is to investigate and assess the impact of various factors on customer loyalty within Indonesian local coffee shops. Specifically, the research aims to explore how value co-creation, product quality, store ambiance, and service quality influence consumer satisfaction. Additionally, the study will examine the relationships among switching costs, customer loyalty, and trust, as well as the mechanisms by which switching costs and trust affect loyalty through the mediating role of satisfaction. Through this comprehensive analysis, the study seeks to provide insights into the dynamics of customer loyalty in the coffee shop industry.Design/Methodology/Approach: In this study, the main quantitative research method was cross-sectional surveys. The hypotheses were assessed using SEM-PLS and Smart PLS.Research findings: The research findings provide valuable insights related to the factors that influence consumer loyalty in the local coffee shop industry in Indonesia, emphasizing the importance of customer satisfaction, switching costs, trust, and the role of mediating factors in fostering long-term loyalty among customersTheoretical Contribution/Originality: The theoretical contribution and originality of the study lie in its exploration of value co-creation, mediating factors, empirical analysis techniques, localized context, and practical implications within the context of consumer loyalty in local coffee shops in Indonesia. These aspects contribute to advancing knowledge in the field of consumer behavior and loyalty within the coffee shop industry.Practitioners/Policy Implications: By implementing these practical implications, practitioners and policymakers in the coffee shop industry can enhance customer satisfaction, build loyalty, and create a competitive advantage in the market. These recommendations aim to improve customer experiences, strengthen relationships, and drive business growth in the local coffee shop sector in Indonesia.Research Limitations/Implications: The research model may have limitations in capturing the full complexity of customer loyalty dynamics. Including additional variables or exploring different theoretical frameworks could provide a more comprehensive understanding of the factors influencing loyalty.